Analisis pegembangan sumber daya manusia pada Kantor Kecamatan Sukamaju Kabupaten Luwu Utara Sulawesi Selatan - Iin Ismayanti (xxxx-xxxx, 2023)
This research aims to determine the development of human resources through education and training carried out by the Sukamaju District office, Kab. North Luwu and to analyze what factors are obstacles to the development of human resources that have been achieved through education and training.This research method uses a qualitative method which is carried out by conducting direct observations to obtain information directly from the leadership and staff at the Sukamaju District Office, North Luwu Regency.Research results: (1) Results of analysis regarding the implementation of human resource development at the Sukamaju District Office, North Luwu Regency, which can be seen from the implementation of training carried out so far which has been quite effective, while the implementation of education has been carried out effectively. (2) The results of the analysis regarding the inhibiting factors currently being faced are the limited human resource development budget received so far and apart from that the training facilities and infrastructure owned by the Sukamaju District Office, North Luwu Regency are relatively limited.